2015
DOI: 10.1103/physrevb.92.064301
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle properties of the nonlinear Holstein model at finite doping and temperature

Abstract: We use determinant quantum Monte Carlo to study the single particle properties of quasiparticles and phonons in a variant of the two-dimensional Holstein model that includes an additional non-linear electron-phonon (e-ph) interaction. We find that a small positive non-linear interaction reduces the effective coupling between the electrons and the lattice, suppresses charge-density wave (CDW) correlations, and hardens the effective phonon frequency. Conversely, a small negative nonlinear interaction can enhance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Nonlinear electron-phonon couplings of Raman-active modes have been prominently featured in MgB 2 33 and investigated theoretically with respect to equilibrium properties in Refs. [34][35][36]. Nonlinear couplings of infraredactive modes have recently been suggested to possibly lead to transient electron-electron attraction by electronic squeezing of phonons, an effect that can be understood via a time-local unitary transformation of the instantaneous Hamiltonian 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear electron-phonon couplings of Raman-active modes have been prominently featured in MgB 2 33 and investigated theoretically with respect to equilibrium properties in Refs. [34][35][36]. Nonlinear couplings of infraredactive modes have recently been suggested to possibly lead to transient electron-electron attraction by electronic squeezing of phonons, an effect that can be understood via a time-local unitary transformation of the instantaneous Hamiltonian 37 .…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, here we explore a new scenario in which phonon dispersion plays a primary role in determining the CDW ordering wavevector and critical temperature, and where SC can supplant diagonal long range order. We extend QMC simulations [14] of a 2D square lattice Holstein Model (HM) to include phonon dispersion [15,16]. In the HM on a bipartite lattice, CDW order dominates over SC at commensurate filling, similar to the dominance of antiferromagnetism over pairing at half-filling in the Hubbard Hamiltonian [17,18].…”
mentioning
confidence: 99%
“…However, small polarons are often accompanied by sizable lattice distortions and a tendency toward localization and charge order. This observation has motivated some work to include higher-order nonlinear e-ph coupling terms to study changes in polaron formation 31 and on charge-density-wave (CDW) and superconducting (SC) pairing correlations 32,33 . These studies found that small positive (negative) nonlinear terms decrease (increase) the effective mass of the carriers and contracts (enlarges) the local lattice distortions surrounding the carriers 31 .…”
mentioning
confidence: 99%
“…These studies found that small positive (negative) nonlinear terms decrease (increase) the effective mass of the carriers and contracts (enlarges) the local lattice distortions surrounding the carriers 31 . Furthermore, mean-field treatments aiming to recover a linear model via effective model parameters fail to capture the quantitative nature of the true nonlinear model [31][32][33] , indicating that nonlinearities cannot be renormalized out of the problem. For example, one can tune the parameters of an effective linear model to capture either the electronic or phononic properties of the nonlinear model but not both simultaneously 33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation